Nuclear Receptors and Endocrine Disruptors in Fetal and Neonatal Testes: A Gapped Landscape - Rouiller-Fabre, Virginie; Guerquin, Marie Justine; N’Tumba-Byn, Thierry; Muczynski, Vincent; Moison, Delphine; Tourpin, Sophie; Messiaen, Sébastien; Habert, René; Livera, Gabriel (Frontiers in Endocrinology, 2015)
During the last decades, many studies reported that male reproductive disorders are increasing among humans. It is currently acknowledged that these abnormalities can result from fetal exposure to environmental chemicals that are progressively becoming more concentrated and widespread in our environment. Among the chemicals present in the environment (air, water, food and many consumer products), several can act as endocrine disrupting compounds (EDCs), thus interfering with the endocrine system. Phthalates, bisphenol A (BPA) and diethylstilbestrol (DES) have been largely incriminated, particularly during the fetal and neonatal period, due to their estrogenic and/or anti-androgenic properties. Indeed, many epidemiological and experimental studies have highlighted their deleterious impact on fetal and neonatal testis development. As EDCs can affect many different genomic and non-genomic pathways, the mechanisms underlying the adverse effects of EDC exposure are difficult to elucidate. Using literature data and results from our laboratory, in the present review we discuss the role of classical nuclear receptors (genomic pathway) in the fetal and neonatal testis response to EDC exposure, particularly to phthalates, BPA and DES. Among the nuclear receptors we focused on some of the most likely candidates, such as peroxisome-proliferator activated receptor (PPAR), androgen receptor (AR), estrogen receptors (ERα and β), liver X receptors (LXR) and small heterodimer partner (SHP). First, we describe the expression and potential functions (based on data from studies using receptor agonists and mouse knockout models) of these nuclear receptors in the developing testis. Then, for each EDC studied, we summarize the main evidences indicating that the reprotoxic effect of each EDC under study is mediated through a specific nuclear receptor(s). We also point-out the involvement of other receptors and nuclear receptor-independent pathways.